UJI ORGANOLEPTIK CRACKERS PISANG TONGKA LANGIT - Priscillia Picauly; Gilian Tetelepta (Universitas Pattimura, 2016)
Tongka langit banana is one of the particular indigenous fruits in Maluku. Tongka langit banana contain high nutrients including pro vitamin A and has a lot of health benefits. However, it is also a perishable product, and would deteriorate if not processed or not completely consumed. Therefore, this banana should be processed into diverse products. It can be processed into intermediate product such as flour, which can be further applied in crackers making. Variables observed on crackers including taste, aroma, colour, texture and overall likeness. Results showed that crackers made from 40% banana flour and 60% wheat flour were mostly liked by panelists in terms of taste, colour, aroma, texture and overall likeness.